Insights and Recommendations From Parents Receiving a Diagnosis of Pediatric Multiple Sclerosis for Their Child. (July 2019) - Hebert, Danielle; Geisthardt, Cheryl; Hoffman, Holly
Forty-two parents of 41 children reported on their experiences receiving a diagnosis of pediatric-onset multiple sclerosis for their child through semistructured phone interviews. Time to diagnosis ranged from 8 hours to 16 years, with the mean age at diagnosis of 13.7 years. The most common initial symptoms included visual disturbances and numbness. The mean number of medical visits to receive a diagnosis was 3.6. Parents reported feeling frustrated and overwhelmed during the diagnosis process, as well as shocked when told their child had multiple sclerosis. Parents emphasized the need for more awareness of pediatric-onset multiple sclerosis. Numerous parents reported encountering physicians who believed multiple sclerosis did not occur in childhood, contributing to a longer time to diagnosis. Parents preferred physicians first share the diagnosis with the parents without the child present. Finally, parents appreciated when physicians provided a variety of resources to help them cope with the diagnosis.